A Recent Profile of HIV-Positive Patients Attending an Integrated Testing and Counseling Centre (ICTC) at a Tertiary Care Center in Bangalore, India - Bhavanarushi Sreekanth1*; Amarendra Goviundu1; Dhanalakshmi A1; Manikonda Rajini1 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: HIV continues to be a significant public health concern worldwide, having claimed over 35 million lives. The Integrated Counseling and Testing Center (ICTC) serves as the entry point to care. HIV-positive individuals referred to ICTC are more likely to practice safer sex and reduce risky behaviors, decreasing the likelihood of transmitting the virus to others. Within this study, we delved into the socio-demographic profile and risk behavior patterns of HIV-positive individuals who sought care at ICTC. Methods: The Oxford Medical College Hospital and Research Center conducted a cross-sectional observational study in a hospital setting. Between July 2018 and January 2020, 7389 individuals were registered at the ICTC. Results: Out of all the clients, 1.04% were HIV reactive. Males had the highest seropositivity rate, accounting for 70.1% of the cases. Seropositivity was most common among individuals aged 35-49 years. Among the seropositive males, 11 (20.3%) were identified as local transport truck drivers. Out of the females included in the study, 16 (69.5%) were identified as housewives. Heterosexual transmission (97.4%) was found to be the most prevalent mode of transmission. Conclusion: As a crucial entry point for HIV prevention, ICTC plays a critical role in promoting awareness through aggressive health education programs and addressing the various needs of people seeking its services.